2002
DOI: 10.1001/jama.287.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes in Adult Patients Receiving Mechanical Ventilation<SUBTITLE>A 28-Day International Study</SUBTITLE>

Abstract: Survival among mechanically ventilated patients depends not only on the factors present at the start of mechanical ventilation, but also on the development of complications and patient management in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
961
17
87

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,537 publications
(1,131 citation statements)
references
References 35 publications
66
961
17
87
Order By: Relevance
“…The mean age of sepsis patients in our study was 66.77 ± 0.14 years, similar to that reported in a prior study [8]. Men accounted for more than half of patients receiving mechanical ventilation, as reported previously [9]. …”
Section: Discussionsupporting
confidence: 89%
“…The mean age of sepsis patients in our study was 66.77 ± 0.14 years, similar to that reported in a prior study [8]. Men accounted for more than half of patients receiving mechanical ventilation, as reported previously [9]. …”
Section: Discussionsupporting
confidence: 89%
“…It remains to be determined whether the alternative approaches liberate patients who use comparable techniques at similar or different time points during weaning. Third, in contrast to the findings of Esteban et al, 20 our respondents preferred to conduct SBTs with techniques that permit adding low levels of PEEP. Use of a T-piece may be a less desirable technique in Canada, as it physically separates the patient from the monitoring capabilities of the ventilator, and it is cumbersome for RTs to assemble.…”
Section: Discussioncontrasting
confidence: 81%
“…3 In contrast to our findings, patients in this study were supported using either AC (55%) or SIMV (26%), and few were managed with PS (8%). In a subsequent observational study involving 5,131 patients in 20 countries, Esteban et al 20 found that once-daily or multiple daily weaning trials were used in 77.8% and 14.0% of weaning attempts. The authors observed that gradual reductions in PS with SIMV, PS or SIMV were utilized in 21.8%, 20.7% and 8.5% of weaning attempts, respectively, and weaning trials were predominantly conducted using T-piece (51.6%), PS (28.2%), and CPAP (19.2%).…”
Section: Discussionmentioning
confidence: 99%
“…B. ventilatorassoziierter Pneumonie (VAP), Atrophie der Atemmuskulatur oder ventilatorinduzierter diaphragmaler Dysfunktion (VIDD) sowie zunehmendem Patientendyskomfort assoziiert, sodass eine prolongierte maschinelle Beatmung mit einer erhöhten Morbidität und Letalität einhergeht [2,4]. Darüber hinaus ist und bleibt die maschinelle Beatmung eine vorübergehende supportive Therapie, die helfen kann, Atem-und Gasaustauschstörungen infolge schwerer akuter Krankheitsbilder wie "acute respiratory distress syndrome" (ARDS), Sepsis, Polytrauma etc.…”
Section: Primäres Ziel: Zeit Gewinnenunclassified